Crusaders - Jones, Rob Lloyd; Illustrated by Cerisier, Emmanuel (London Usborne Publishing, 2007)
Lively account of the Crusaders, with exciting descriptions of the main people, places and battles, including the peasant's crusade and the siege of Jerusalem. Young Reading Series Three are for confident readers who still need to gain the stamina needed for standard length books.
Include Color Illustrations
Keywords: Crusades